A recent large-scale intraspecific IR expansion and evolutionary dynamics of the plastome of Peucedanum japonicum - Ho Jun Joh; Young Sang Park; Jong-Soo Kang; Jin Tae Kim; Jickerson P. Lado; Sang Il Han; Young-Won Chin; Hyun-Seung Park; Jee Young Park; Tae-Jin Yang (Scientific Reports)
Abstract Peucedanum japonicum (PJ), a member of the Apiaceae family, is widely distributed and cultivated in East Asian countries for edible and functional foods. In this study, we compared the plastid genomes (plastomes) and 45S nuclear ribosomal DNA (45S nrDNA) simultaneously from 10 PJ collections. Plastome-based phylogenetic analysis showed that the PJ accessions were monophyletic within the genus Peucedanum. However, ten plastomes were classified into two different groups according to their length of inverted repeat (IR) block, the short-type (S-type) plastome group containing the 18.6 kbp of the original IR and the long-type (L-type) plastome group containing the 35.7 kbp of expanded IR by duplication of the 17.1 kbp of the large single copy region. A total of nine single nucleotide polymorphisms and eight insertions or deletions were identified among the five L-type plastomes, whereas large variations were identified among the five S-type plastomes. Calculation of synonymous substitution rates and divergence time estimation suggested that the 17 kbp IR expansion occurred recently. Molecular markers were developed and validated to classify the 55 PJ germplasm according to their plastome types. Our study would be useful for unraveling the dynamic evolution of plastomes in the Apiaceae family and for the molecular breeding of PJ.